2011
DOI: 10.1161/strokeaha.110.610915
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use, Ischemic Stroke, and Multifocal Intracranial Vasoconstriction

Abstract: Background and Purpose-Our objective was to evaluate the relationship between cannabis use and ischemic stroke in a young adult population. Methods-Forty-eight consecutive young patients admitted for acute ischemic stroke participated in the study. First-line screening was performed, including blood tests, cardiovascular investigations, and urine analysis for cannabinoids. If no etiology was found, 3D rotational angiography and cerebrospinal fluid analysis were performed. A control was planned through neurovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 7 publications
4
127
2
9
Order By: Relevance
“…The attenuated decreases in DV with MP in the marijuana abusers were observed throughout the brain but were most accentuated in cerebellum. The higher sensitivity of the cerebellum to what we interpret to reflect changes in vascular reactivity with marijuana abuse is consistent with clinical findings that report strokes associated with marijuana abuse are more frequently localized in the posterior circulation and ischemia is most frequently observed in cerebellum (25,(54)(55)(56). Cerebellar arteries express CB1 receptors in the smooth muscle layer (57), but because comparisons with arteries in other brain regions have not been done, it is not possible to determine if higher levels of CB1 receptors in cerebellar arteries underlie their higher sensitivity to vascular effects from marijuana.…”
Section: Mp-induced Changes In DVsupporting
confidence: 90%
“…The attenuated decreases in DV with MP in the marijuana abusers were observed throughout the brain but were most accentuated in cerebellum. The higher sensitivity of the cerebellum to what we interpret to reflect changes in vascular reactivity with marijuana abuse is consistent with clinical findings that report strokes associated with marijuana abuse are more frequently localized in the posterior circulation and ischemia is most frequently observed in cerebellum (25,(54)(55)(56). Cerebellar arteries express CB1 receptors in the smooth muscle layer (57), but because comparisons with arteries in other brain regions have not been done, it is not possible to determine if higher levels of CB1 receptors in cerebellar arteries underlie their higher sensitivity to vascular effects from marijuana.…”
Section: Mp-induced Changes In DVsupporting
confidence: 90%
“…9 There is no specific antidote for marijuana intoxication, but in cases of severe anxiety symptoms or a panic attack, treatment with a benzodiazepine may help, 9 and supportive treatment is used for oversedation. 10 Ischemic stroke in young people has also been reported. 11 No fatalities have ever been reported as solely attributable to a marijuana overdose; however, ingestion of marijuana by children can result in a variety of symptoms, including drowsiness, ataxia, nystagmus, hypothermia, and hypotonia.…”
Section: Side Effects Of Marijuana Usementioning
confidence: 99%
“…12 Since the legalization of medical marijuana in Colorado, a number of reports of children with toxic ingestions have occurred. 10 Treatment with activated charcoal to prevent absorption of the marijuana may be helpful in specific severe situations if there is no concern about level of consciousness and if treatment is initiated well within 2 hours of onset of the ingestion. As with any other prescribed medication for adults, children should not have access to medical marijuana, with the exception of unique circumstances discussed later.…”
Section: Side Effects Of Marijuana Usementioning
confidence: 99%
“…Of the 142 studies identified, thirty-six did not meet the a priori selection criteria [33, and sixty-two met the exclusion criteria [6,12,30,48, or were case/series reports [142] (for more detailed information, see Figure 1). The remaining 43 studies were classified according to the neuroimaging technique used (structural/functional), age of the participants [adolescents (# 18 years) and adults (.…”
Section: Resultsmentioning
confidence: 99%